PROGRAM JAM WAJIB BELAJAR DALAM MEMBENTUK CIVIC DISPOSITION WARGA NEGARA - Mufidah, Nastiti (HUMANIKA, 2016)
The purpose of this research to analyze the formation of civic disposition through compulsory Hours Learning Program, as well as knowing the character of the citizens who were able to form through the Compulsory program clock. Informants in this research is a community in Mojokerto city. Qualitative approach with case study method used in this study. Furthermore, the data collection techniques used interviews, observations and questionnaires. The results in this study indicate that the Compulsory Education Program Hours proven capable of forming civic disposition citizens. Civic disposition can be formed based on the results of this study the character of discipline and care, while other characters such as responsibility and tolerance still can’t set up perfectly.